2012
DOI: 10.1007/s00299-012-1262-8
|View full text |Cite
|
Sign up to set email alerts
|

ZmHSP16.9, a cytosolic class I small heat shock protein in maize (Zea mays), confers heat tolerance in transgenic tobacco

Abstract: The overexpression of ZmHSP16.9 enhanced tolerance to heat and oxidative stress in transgenic tobacco.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 45 publications
4
85
0
Order By: Relevance
“…Despite the apparent requirement of both CI and CII HSPs for optimal heat tolerance, as demonstrated by the RNAi experiments, constitutive expression of either class alone enhanced the greening of dark-grown seedlings after direct heat stress (basal thermotolerance), consistent with previous reports using different assays to test the heat stress tolerance of plants constitutively expressing CI or CII sHSPs (Sun et al, 2012;Zhou et al, 2012;Wang et al, 2015). We also observed that, even though endogenous sHSPs are highly expressed in heat-acclimated plants, the individual sHSP OE lines had a still higher survival rate than the wild type after heat stress following acclimation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the apparent requirement of both CI and CII HSPs for optimal heat tolerance, as demonstrated by the RNAi experiments, constitutive expression of either class alone enhanced the greening of dark-grown seedlings after direct heat stress (basal thermotolerance), consistent with previous reports using different assays to test the heat stress tolerance of plants constitutively expressing CI or CII sHSPs (Sun et al, 2012;Zhou et al, 2012;Wang et al, 2015). We also observed that, even though endogenous sHSPs are highly expressed in heat-acclimated plants, the individual sHSP OE lines had a still higher survival rate than the wild type after heat stress following acclimation.…”
Section: Discussionsupporting
confidence: 90%
“…However, only single alleles were tested, and no complementation experiments were performed. Further evidence for the stress-protective role of CI and CII sHSPs in plants has primarily involved constitutive expression or overexpression of a single sHSP in different plant species, including Arabidopsis, rice (Oryza sativa), maize (Zea mays), and carrot (Daucus carota), as well as others (Malik et al, 1999;Ahn and Zimmerman, 2006;Jiang et al, 2009;Sun et al, 2012;Zhou et al, 2012;Mu et al, 2013;Wang et al, 2015). A very restricted set of stress-resistant phenotypes has been reported for sHSP-overexpressing transgenic materials, and these studies have not provided mechanistic insight into sHSP function or distinguished differences between CI and CII sHSPs.…”
mentioning
confidence: 99%
“…According to Sun et al (2012), water stress induces heat-resistant protein expression, such as HSP. Ristic et al (1991) found a HSP band of approximately 45 kDa in maize leaves from a heat and water stress-tolerant line.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, 8 Hsp100 members (Agarwal et al, 2001), 7 Hsp90 members (Krishna and Gloor, 2001), 18 Hsp70 members (Lin et al, 2001), 11 Hsp60 members (Hill and Hemmingsen, 2001), and 13 sHsps members (Scharf et al, 2001) have been identified in the genome and analyzed. Hsps from different families have been also reported in other plant species, such as cereals (Maestri et al, 2002), maize (Sun et al, 2012), and wheat (Kumar et al, 2012). Modifying the expression of Hsp via genetic engineering has been shown to be useful for enhancing temperature stress tolerance in plants.…”
Section: Introductionmentioning
confidence: 93%